Optimization of tropical rainforest ecosystem management: implications from the responses of ecosystem service values to landscape pattern changes in Hainan Tropical Rainforest National Park, China, over the past 40 years - Lin, Xiaofu; Fu, Hui (Frontiers in Forests and Global Change, 2023)
Exploring the comprehensive impact of landscape pattern changes on regional ecosystem service values (ESVs) over a long time series is significant for optimizing ecosystem management. This study took Hainan Tropical Rainforest National Park (HTRNP) as a case and first assessed its five vital ecosystem services (ESs): water supply (WS), water purification (WP), carbon storage (CS), soil retention (SR), and habitat quality (HQ). Based on the ESs assessment results, we further calculated their ESVs and quantified the responses of ESVs to landscape pattern changes during 1980–2020. The results revealed that: (1) Forestland is the basal landscape type of HTRNP. Landscape patterns changed significantly after 2000; the proportion of both cultivated land and grassland decreased, while the proportion of forestland, water, and construction land increased; with the areas and landscape dominance of both forestland and water increased, the agglomeration and connectivity of the overall landscape increased and its homogenization decreased. (2) WS, WP, CS, and SR services tended to weaken, and HQ service tended to strengthen. The spatial heterogeneities of WS and SR changed significantly over time. WS, HQ, SR, and CS are the main contributors to the total ESV. During 1980–2020, the four ESVs of WS, WP, SR, and CS showed a decreasing trend; HQ’s ESV tended to increase, and the total ESV tended to decrease. (3) The increase of areas and dominance in forestland and water was the main reason that HQ’s ESV tended to increase, and WP’s ESV and CS’s ESV tended to decrease. The construction land scale was relatively small, so its impacts on ESVs were limited. The responses of both WS’s ESV and SR’s ESV to landscape pattern changes were insignificant due to the impacts of topographic and climatic factors. The study results provide a reference for managing and optimizing HTRNP’s ecosystem to improve its integrated benefits of crucial ESs.